Shelf-life and Microbiological Profiler of Chicken Wing Products Following Sous vide Treatment - Wang, S.H.; Chang, M.H.; Chen, T.C. (International Journal of Poultry Science, 2004)
Chicken wings were vacuum-packaged and cooked (sous vide) at 75 and 90°C until the internal temperature reached 73.8°C was reached. The cooked samples were stored at 2 and 7°C, separately. The TBA values, aerobic plate count, aerobic and anaerobic plate counts and Warner-Bratzler (WB) shear force of the samples were evaluated weekly for 7 wk. The sous vide treatment chicken wings had lower TBA values, aerobic and anaerobic plate counts throughout the 7 wk of storage when compared with the control. The sous vide treatment did not affect the WB shear force of chicken wings. At 2°C, the sous vide cooked chicken wings had a shelf life of at least 7 wk. Results demonstrate that sous vide treatment was an effective method to prevent lipid oxidation during storage and enhance shelf life of chicken wing products.